2005
DOI: 10.1143/jjap.44.139
|View full text |Cite
|
Sign up to set email alerts
|

Density Distribution Profiles of Excess Minority Carriers Injected with 904-nm-Wavelength Laser Pulse into 400-µm-Thick Silicon Wafer

Abstract: Angular distributions of two alpha-particle groups from the reaction 24Mg(3He, a)23Mg at 5.5 MeV incident beam energy have been measured by magnetic analysis. For both groups a peak is observed in the forward direction, but for one of the groups an additional peak is observed at large angles of observation. An attempt has been made to explain the results in terms of a direct interaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It should be noted that sp tends towards the first value of 14 ms. All vp 's are around 1.7 ms and fairly constant as theoretically expected. 1,8) They are, however, a little bit longer than the first one of 1.3 ms.…”
mentioning
confidence: 89%
“…It should be noted that sp tends towards the first value of 14 ms. All vp 's are around 1.7 ms and fairly constant as theoretically expected. 1,8) They are, however, a little bit longer than the first one of 1.3 ms.…”
mentioning
confidence: 89%
“…On the other hand, lead-free piezoelectric ceramics, such as (K,Na)NbO 3 (KNN)-based ceramics, (Bi 0:5 Na 0:5 )-TiO 3 -based ceramics, [24][25][26][27] (Bi 0:5 K 0:5 )TiO 3 -based ceramics, 25,28) ferroelectric ceramics with a tungsten bronze structure, 29) and bismuth layer-structured ferroelectrics [30][31][32][33] have been extensively studied recently, and several candidates were proposed in the basic research stage. In our recent study, we also proposed KNN-based multilayer piezoelectric ceramics with nickel inner electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…1) Since the discovery of high-mobility organic materials, 2,3) many theoretical and experimental studies have been carried out to clarify the operation of OFETs. [4][5][6][7][8] The performance of OFET has remarkably advanced, and many important aspects concerning the operation mechanism of OFETs have been discovered. For example, it was found that carrier injection dominates the OFET characteristics 9,10) and that ambipolar operation is observed in many OFETs.…”
Section: Introductionmentioning
confidence: 99%